Improving mental health care in rural Kenya: A qualitative study conducted in two primary care facilities. Issue 4 (2nd October 2022) - D'Orta, Isabella; Eytan, Ariel; Saraceno, Benedetto
Abstract: Mental health research is needed in African countries in order to improve quality of care at local levels. This paper presents the results of a study conducted in 2018 among one hundred care givers in two peripheral primary health care facilities in rural Kenya. Opened interviews were performed, with the aim of eliciting relevant issues. The body of knowledge generated by the Global Mental Health (GMH) movement was used as the theoretical frame of reference. Five broad topics emerged as particularly significant in the specific context of this study: a. a globally negative perception of mental illness; b. a lack of trained professionals associated with limited opportunities for task-sharing or task-shifting; c. an intense stigmatization of affected individuals; d. the importance of strengthening the collaboration between the formal health sector and traditional healers, and, e. the necessary efforts to be made in order to reach patients living in remote areas. Our study highlights the importance of actively detecting mental disorders, promoting initiatives to reduce stigma and adapting western designed tools for specific settings in low and middle income countries (LMICs).